Independent tephrochronological evidence for rapid and synchronous oceanic and atmospheric temperature rises over the Greenland stadial-interstadial transitions between ca. 32 and 40 ka b2k. (15th May 2020) - Berben, Sarah M.P.; Dokken, Trond M.; Abbott, Peter M.; Cook, Eliza; Sadatzki, Henrik; Simon, Margit H.; Jansen, Eystein
Abstract: Understanding the dynamics that drove past abrupt climate changes, such as the Dansgaard-Oeschger (DO) events, depends on combined proxy evidence from disparate archives. To identify leads, lags and synchronicity between different climate system components, independent and robust chronologies are required. Cryptotephrochronology is a key geochronological tool as cryptotephra horizons can act as isochrons linking disparate and/or distant records. Here, we investigated marine sediment core MD99-2284 from the Norwegian Sea to look for previously identified Greenland ice core cryptotephra horizons and define time-parallel markers between the archives. We explored potential secondary transport and depositional mechanisms that could hamper the isochronous integrity of such horizons. We identified six cryptotephra layers of which four correlate to previously known Greenland ice core horizons. None of those were identified in other marine cores and thus, this study contributes greatly to the North Atlantic tephra framework tripling the original amount of existing isochrons between ca. 25 and 60 ka b2k. The latter allow a synchronization between MD99-2284 and the Greenland ice cores between ca. 32–40 ka b2k, which is, in the North Atlantic, the shortest time-interval during the Last Glacial Period to be constrained by four independent tephra isochrons. These findings provide essential tephra-based evidence for synchronous and rapid oceanic and atmospheric temperature rises during the Greenland Stadial-Interstadial transitions. Furthermore, it enables us to estimate the average peak-duration of interstadial temperature overshoots at approximately 136 years. As such, this well-targeted high-resolution investigation successfully demonstrates the use of cryptotephra for geochronological purposes in the marine realm. Highlights: Six distinct cryptotephra deposits are discovered for the first time in marine sediment core MD99-2284. The existing amount of isochrons between ca. 25 and 60 ka b2k is tripled by four new ones. Four new tephra isochrons allow for a highly detailed synchronization of disparate palaeo records. Oceanic and atmospheric temperature changed synchronously over the GS-GI transitions. The average peak-duration of interstadial temperature overshoots is estimated at ca. 136 years.